PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 22 DURI BARAT KECAMATAN MANDAU - Wahyuli Rojis; Mahmud Alpusari; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak : This research was conducted because of the result of learning social study class III B SD Negeri 22 Duri Barat. From  30 students who achieve  KKM just 12 students ( 40%) while students who did’nt complete 18 students (60%) with an average of  64,5. The purpose of this research to improve learning outcomes IPS class III B SD Negeri 22 Duri Barat with the application of learning models snowball throwing. The results obtained by the average value of 64,5 basic score increased in the first cycle of 18,29% to 76,3. In the second cycle the average value of students also increased by 32,6% to 85,6. On the basic of completeness score IPS student learning outcomes is only 60% (not finised). After the professor of applied learning model snowball throwing in the first cycle classical  completeness  increased  to 73% (not finised), the second cycle of classical completeness obtained are increased to increase to 87%. Activities of teachers at the first meeting of 75% with both categories. The second meeting increased 87,5% in the both categories. In the second cycle increased to 91,67% with the category very well. At a meeting of the second meeting of the second cycle, the activities of teachers in creased to 95,83% with category very well. Activities of students in the first cycle of the first meeting activity students acquire a percentage of 70,83% n both categories. The second meeting of the first cycle to 79,17% in both categories. At the first meeting of the second cycle of student activity ncreased to 87,5% in both categories and at the second meeting of the second cycle increased again to 95,83% with the category very  well. Key Words : Snowball Throwing, learning outcomes IPS